Interaction between Intellectual Capital Components in Firm’s Value Creation Process - Юлия Николаевна Найденова; Марина Александровна Осколкова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Authors: Yulia Nikolayevna Naydenova National Research University The Higher School of Economics yunaydenova@hse.ruMarina Alexandrovna Oskolkova National Research University The Higher School of Economics moskolkova@hse.ruAccording to the theory of the knowledge economy, the most important resource of firms and other economic agents are knowledge and tools of its management, which are usually called "intellectual capital". On the other hand, following the concept of value-based management (VBM), the main objective of the company is an increase of its value for all stakeholders. Therefore, for effective company’s management it is important to understand how intellectual capital (IC) contributes to the process of value creation. This paper deals with the interaction of IC components in the value creation. Using the sample of panel data consisting of 64 British companies over the period of 2005-2009, we revealed that there is a synergistic effect of simultaneous use of different components of the IC. In addition the structure of intellectual capital could affect created company’s value added.